Julio Cortázar, Carlos Fuentes, Gabriel García Márquez y Mario Vargas Llosa, Las cartas del Boom (editado por Carlos Aguirre, Gerald Martin, Javier Mungía y Augusto Wong Campos) - Ribadero, Martín (Prismas - Revista de historia intelectual, 2025)
Julio Cortázar, Carlos Fuentes, Gabriel García Márquez y Mario Vargas Llosa, Las cartas del Boom (editado por Carlos Aguirre, Gerald Martin, Javier Mungía y Augusto Wong Campos)